Alternative Interim Reporting Techniques Within a Dynamic Framework: A Reply. - Fried, Dov; Livnat, Joshua (The Accounting Review, 1985)
The article presents reply from authors issues related to alternative interim reporting techniques within a dynamic framework. Professor William S. Hop wood and Paul Newbold criticize the single-period setting and the single-signal-reporting system. In their analysis, they show by counter-examples that when one adopts a multiperiod world, both the integral and the combination method may result in an infinite variance when the reporting objective is to predict the current period earnings. The intuition behind is that when managers have perfect foresight and the reports always contain half of the annual totals, investors are unable to allocate correctly the annual total among the interim periods, if one assumes that the process generating earnings is seasonal. Moreover, since investors have access to other information for breaking down the annual totals, the information set in the beginning of the period may not be as method-dependent. For example, many industry sales and earnings data are reported for interim periods by trade associations. Users can thus derive prior distributions and form expectations regarding interim results from a combination of industry and firm data. Thus, the prior distributions may not be so different, even if different reporting methods had been used in prior periods.